2018
DOI: 10.1088/1748-9326/aae5d7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring what works: quantifying greenhouse gas emission reductions of behavioural interventions to reduce driving, meat consumption, and household energy use

Abstract: Interventions that promote pro-environmental behaviours are increasingly necessary in reducing use of high-emissions goods and services to meet international climate change targets. Here we assess the greenhouse gas emissions reductions associated with behavioural interventions in three high-emitting domains (personal vehicle use, meat consumption, and household energy use) based on an analysis of the peer-reviewed literature. We examined 40 studies from 1991-2018 involving 886 576 subjects. We found that some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 114 publications
3
55
0
5
Order By: Relevance
“…When psychologists interested in pro-environmental behaviors neglect looking in detail at impacts, they risk reinforcing existing popular misperceptions of TP. For example, a recent review of behavioral interventions that promote pro-environmental behavior was unable to identify any interventions aiming to reduce air travel despite it being one of the highest GHG-emitting individual behaviors and one that is rapidly increasing (Wynes et al, 2018).…”
Section: The Challenge Of Misplaced Focusmentioning
confidence: 99%
“…When psychologists interested in pro-environmental behaviors neglect looking in detail at impacts, they risk reinforcing existing popular misperceptions of TP. For example, a recent review of behavioral interventions that promote pro-environmental behavior was unable to identify any interventions aiming to reduce air travel despite it being one of the highest GHG-emitting individual behaviors and one that is rapidly increasing (Wynes et al, 2018).…”
Section: The Challenge Of Misplaced Focusmentioning
confidence: 99%
“…How would the cost and benefits of such an intervention compare to similar interventions targeting meat consumption in broader dietary contexts? Recent research has begun to compare different experimental interventions aimed at encouraging individuals to reduce their meat consumption [20]. One study, implemented in a student catering facility, found that providing information about the carbon footprint of various food choices resulted in a 4.8 percentage point reduction in meat dishes labeled with high emissions-but an 11.5 percentage point increase in meat dishes labeled as having low emissions-leading to an estimated 3.6 percentage point reduction in emissions [21].…”
Section: Introductionmentioning
confidence: 99%
“…Without systematic logging and tracking of study design and results, however, academics and practitioners will continue to face the same challenges of synthesizing the vast amount of existing information. Wynes et al (2018) provided an example of a better way to understand impacts across studies by quantifying their greenhouse gas emissions reductions [97]. Providing a weight in kilograms, of reduced carbon dioxide, goes a step further than effect sizes to measure intervention impacts.…”
Section: Knowledge Accumulationmentioning
confidence: 99%
“…Logging the results of behavioral intervention studies on a publicly available database would advance accumulation of knowledge in the field. Studies like Wynes et al (2018) would have a much larger pool of data to draw from when conducting quantitative analyses. Additionally, tracing unpublished interventions in the database may work to combat publication bias that favors positive results, much like the way clinical trials must be registered before they are completed [98].…”
Section: Knowledge Accumulationmentioning
confidence: 99%